Advances in steroid sparing medical management of active thyroid eye disease. (18th May 2020) - Liou, Victor D.; Yoon, Michael K.
ABSTRACT: Thyroid eye disease (TED) is an autoimmune inflammatory disease of the orbit and the most common extrathyroidal manifestation of Graves disease. The release of pro-inflammatory cytokines is associated with inflammation of the ocular surface and lacrimal gland along with periorbital skin erythema and edema. Resultant tissue remodeling, fibrosis, and fat deposition can impart permanent physical changes to the ocular adnexa with effects on function and cosmesis. These changes occur in the active phase of disease, and it is during this time that steroids are often relied on to help alleviate symptoms. Due to the common and predictable side effects of long-term and high-dose steroid use, there has been a continuous effort to find alternative steroid-sparing medical management options for TED. This review highlights the various research studies that support the use of these medications.